Role-Playing Methods to Improve Early Childhood's Emotional Abilities - sulis, Sulistianingsih; Ratini; Permana, Hara; Maulidah, Idah; Ali Fauzi Ahmad Khan (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
Educational stimuli that are considered to have an essential role in children's lives from an early age are emotional development. Emotional development is related to all aspects of child development. Young children tend to express their emotions freely or openly at this stage. This research aims to see the role-play method's effectiveness in improving young children's emotional abilities at school. This research uses an experimental method with a quasi-experiment type and a quantitative approach. Data were collected using a pre-test and post-test on 25 children. The difference in the emotional abilities of Group A children in PAUD Nurus Syifah Sumber, Cirebon Regency, before and after implementing the role-playing method is proven by the tcount = 14.687. This value is compared with the ttable at db = 25-2 = 23 with a significance of 0.05 (5%), resulting in a ttable of 1.714. Based on the provisions, if tcount > ttable, then H0 is rejected. Thus, it can be seen that tcount > ttable (14.687 > 1.714), which means that H0 (null hypothesis) is rejected, meaning that there is a significant difference in children's emotional abilities before and after implementing the role-playing method with a difference level of 56% which means that children's emotional abilities are more significant. Good when using role-playing methods. This research concludes that the role-playing method can improve the emotional abilities of young children